A review of cetacean interactions with longline gear - Gilman, Eric; Brothers , Nigel; McPherson , Geof; Dalzell , Paul (J. Cetacean Res. Manage., 2023)
Fishery-cetacean interactions, including those with longline gear, give rise to economic, ecological and social concerns. This paper reviews problems resulting from cetacean-longline interactions, considers potential strategies to reduce interactions and identifies research priorities and approaches. Depredation by cetaceans (removal and damage of hooked fish and bait from fishing gear) and damage and loss of fishing gear create economic problems; however, the magnitude of this problem is poorly understood. There is also insufficient information to determine whether there are population-level effects resulting from injury and mortality of cetaceans (from incidental entanglement and hooking and from deliberate actions to discourage depredation). Fishery-cetacean interactions may also: change cetacean foraging behaviour and distribution; increase fishing effort to make up for fish taken from gear by cetaceans; and create errors in fish stock assessments that do not account for cetacean depredation. Negative public perceptions of longline fishing can result from news of incidental and deliberate injury and mortality of cetaceans associated with longlining. Information on how to reduce cetacean interactions with longline gear is also limited, as is the understanding of the mechanisms responsible for them. Strategies already employed in some fleets include refraining from setting or cutting sets short when problematic species of cetaceans are observed and fleet coordination of daily fishing times and positions. Many fishermen perceive depredation as an inevitable part of fishing. This paper discusses a number of other possible cetacean avoidance strategies that warrant consideration, including: (1) fleet communication to enable vessels to avoid temporally and spatially unpredictable and sporadic hotspots of aggregations of cetaceans; (2) underwater acoustic masking devices to conceal the sound of the vessel, gear, and setting and hauling activities; (3) quieter vessels to reduce cetaceans’ ability to target longline vessels; (4) encasement of caught fish to reduce cetacean access to or interest in the catch; (5) use of bait or gear with an unpleasant smell or taste to reduce the attractiveness of gear, bait and catch to cetaceans; (6) use of pre-recorded fishing vessel sounds played from stations throughout a fleet’s fishing grounds to distract cetaceans from actual fishing vessels; (7) use of acoustic devices to mask returning cetacean echolocation signals; and (8) use of tethered sonobuoys to track cetaceans and enable fleet avoidance. Vessels with relatively low cetacean interaction rates should be examined for design and operational differences from vessels with high interaction rates, possibly allowing identification of effective avoidance methods. There is a need for experimentation in individual longline fisheries over several seasons to assess fisheryspecific efficacy and commercial viability of cetacean avoidance strategies. This is necessary as different cetacean species likely respond differently to an avoidance method and cetaceans may habituate to an avoidance strategy, especially in fisheries interacting with resident cetaceans.